Determinação de ratings de crédito de unidades de negócios visando estimar o custo de capital de terceiros - Sanvicente, Antonio Zoratto (2007)
A methodology for the estimation of credit rating in business and firms is provided. Credit ratings were colected from Moody's and Standard&Poor's Institutional Market Services and from several accounting and market variables with regard to 627 U.S. firms. A logistic model was employed so that variables that best explained the firm's credit rating could be selected and, at the same time, a classification model for credit rating could be introduced. Third party's capital costs may be associated with each credit rating its term. Credit rating may be determined by knowing the characteristics of each firm, business or project, loan termis and third party's capital costs market values. The above instrumetns are strategically of prime importance since they contribute to determine with preciseness the firm's capital costs and identify the structure of capital that decreases the costs of asset collection and consequently increases values for shareholders. Since the performance of main executive is measured by value introduction measurements, with each variant being the capital's mean costs, currnet procedure better adjusts recompense to strategy and value introduction for the shareholder.